Altered Gut Microbiota Composition Associated with Eczema in Infants. - Huajun Zheng; Hong Liang; Yuezhu Wang; Maohua Miao; Tao Shi; Fen Yang; Enuo Liu; Wei Yuan; Zai-Si Ji; De-Kun Li (PLoS ONE, 2016)
Eczema is frequently the first manifestation of an atopic diathesis and alteration in the diversity of gut microbiota has been reported in infants with eczema. To identify specific bacterial communities associated with eczema, we conducted a case-control study of 50 infants with eczema (cases) and 51 healthy infants (controls). We performed high-throughput sequencing for V3-V4 hypervariable regions of the 16S rRNA genes from the gut fecal material. A total of 12,386 OTUs (operational taxonomic units) at a 97% similarity level were obtained from the two groups, and we observed a difference in taxa abundance, but not the taxonomic composition, of gut microbiota between the two groups. We identified four genera enriched in healthy infants: Bifidobacterium, Megasphaera, Haemophilus and Streptococcus; and five genera enriched in infants with eczema: Escherichia/Shigella, Veillonella, Faecalibacterium, Lachnospiraceae incertae sedis and Clostridium XlVa. Several species, such as Faecalibacterium prausnitzii and Ruminococcus gnavus, that are known to be associated with atopy or inflammation, were found to be significantly enriched in infants with eczema. Higher abundance of Akkermansia muciniphila in eczematous infants might reduce the integrity of intestinal barrier function and therefore increase the risk of developing eczema. On the other hand, Bacteroides fragilis and Streptococcus salivarius, which are known for their anti-inflammatory properties, were less abundant in infants with eczema. The observed differences in genera and species between cases and controls in this study may provide insight into the link between the microbiome and eczema risk.